Analisis strategi peningkatan daya saing pada UKM Anugrah Mina Lestari - Dayang Diah Fidhiani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
UKM Anugrah Mina Lestari is an UKM that processes milkfish into smoked milkfish products and millennial milkfish brains, which are very popular, especially children and teenagers. Anugrah Mina Lestari UKM in Malang City plays an important role in national economic growth. The purpose of this study was to obtain a strategy to increase the competitiveness of UKM Anugrah Mina Lestari in Malang City. Technical analysis of this research data using the AHP method with the concept of the house model to determine strategies to increase the competitiveness of SMEs Anugrah Mina Lestari in Malang City. The results of the study show that by increasing product variables, improving human resources and marketing institutions can be a strengthening strategy for sustainable competitiveness improvement in Anugrah Mina Lestari SMEs.